PENERAPAN NORMA HUKUM NAFKAH IDDAH DALAM PERKARA CERAI GUGAT: ANALISIS RATIO DECIDENDI PUTUSAN HAKIM PENGADILAN AGAMA - Nur Aini Asri Devi; Ali Khosim; Riyan Ramdani (LPPM STAI Muhammadiyah Probolinggo, 2026)
Iddah alimony is a post-divorce right received by the wife. Iddah alimony due to talaq is specifically regulated in Article 149 of the Compilation of Islamic Law (KHI), while the regulations on ifdah alimony for divorce have not been explicitly contained in a regulation. Because of this gap, the government issued SEMA No. 3 of 2018 as a regulation to protect the rights of wives in divorce lawsuits. However, instead of applying SEMA a quo in legal considerations, the council of judges in several judgments of iddah alimony divorce prefer to use articles 149 of the Code of Civil Code or 152 of the Code of Civil Procedure, even though the two articles normatively only apply to the consequences of talaq. The purpose of this study is to find out the practice of applying the norm of iddah alimony by judges in the Religious Court in the divorce decree and analyze its conformity with the applicable positive law. The research method used is normative legal research that focuses on examining the rules and norms of law in positive law. The results of the study show that the application of articles 149 and 152 of the KHI is not appropriate in adjudicating the maintenance of the divorce lawsuit, and has violated the principle that the decision must contain a correct and appropriate legal basis or reason as contained in article 50 paragraph 1 of Law Number 48 of 2009 concerning Judicial Power. This research is expected to be an input for judges in religious courts regarding the application of legal norms of alimony, and as a new breakthrough for lawmakers to form regulations regarding the legal consequences of divorce lawsuits.